2016
DOI: 10.1007/s13142-016-0393-9
|View full text |Cite|
|
Sign up to set email alerts
|

Development and refinement of a clinician intervention to facilitate primary care patient use of the PTSD Coach app

Abstract: Posttraumatic stress disorder (PTSD) is common and undertreated among Veterans Affairs (VA) primary care patients. A brief primary care intervention combining clinician support with a self-management mobile app (Clinician-Supported PTSD Coach, CS-PTSD Coach) may improve patient outcomes. This study developed and refined an intervention to provide clinician support to facilitate use of the PTSD Coach app and gathered VA provider and patient qualitative and quantitative feedback on CS-PTSD Coach to investigate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 35 publications
0
76
0
3
Order By: Relevance
“…The studies also cover diverse disease areas and medical specialties, including ambulatory care [ 58 ], cognitive behavioral therapy [ 40 ], cardiovascular disease [ 56 , 83 ], dermatology [ 73 ], diabetes [ 50 , 63 , 65 ], general practice [ 35 , 52 , 59 ], intensive care [ 36 ], neurology [ 48 ], pediatric [ 45 ], primary and acute care [ 46 , 49 , 55 , 71 , 74 ], psychiatry and mental health [ 41 , 53 , 68 ], residential aged care [ 57 ], reproductive health [ 37 ], and substance use recovery [ 39 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies also cover diverse disease areas and medical specialties, including ambulatory care [ 58 ], cognitive behavioral therapy [ 40 ], cardiovascular disease [ 56 , 83 ], dermatology [ 73 ], diabetes [ 50 , 63 , 65 ], general practice [ 35 , 52 , 59 ], intensive care [ 36 ], neurology [ 48 ], pediatric [ 45 ], primary and acute care [ 46 , 49 , 55 , 71 , 74 ], psychiatry and mental health [ 41 , 53 , 68 ], residential aged care [ 57 ], reproductive health [ 37 ], and substance use recovery [ 39 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…DOI was used in 16% (8/50) of the studies [ 37 , 40 , 50 , 53 , 56 , 62 , 76 , 78 ], and UTAUT extensions were used in 12% (6/50) of the studies; some of these UTAUT extensions were based on the research context and previous research [ 64 , 66 , 84 ], and other included extensions from other frameworks such as the De Lone and McLean information success model [ 54 ], use of technology [ 65 ], and a combination of TAM, TPB, and DOI [ 82 ]. Furthermore, certain studies used a combination of the TAM and DOI frameworks (3/50, 6%) [ 42 , 43 , 59 ]; others used the consolidated framework for implementation research (CFIR; 3/50, 6%) [ 39 , 41 , 67 ] and the STS (2/50, 4%) [ 49 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating personalized feedback to the end‐user is recommended to increase the usability and sustained use of posttrauma mobile screeners (Price et al, ). In addition, these tools would be even more valuable if they provide contact details of professional health care institutions (Olff, ; Price et al, ) and are linked to other evidence‐based mobile apps, such as the PTSD Coach that offers self‐help to individuals with PTSD symptoms (Kuhn et al, ; Miner et al, ; Owen et al, ; Possemato, Kuhn, Johnson, Hoffman, & Brooks, ). In this manner, the needs of trauma survivors can be (timely) met and the appropriate posttrauma care can be delivered and received (Olff, ; Owen et al, ; Price, Ruggiero, et al, ; Price, Yuen, et al, ; Price et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…to understand the degree and ways in which the features and manifestations of the environment influence public health and aspects of our lifestyle in cities [194,195]. Computer scientists are recently gaining importance in the field as the increasing democratisation and deployment of mobile computing, mobile devices and sensing technologies [196] provide new opportunities to deliver mobile mental health care [197][198][199] thus improving quality of life [200]. Various authors [199,201,202] have suggested that interventions with mobile phones designed to support evidence-based treatments could even reduce barriers to access and increase participation in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Computer scientists are recently gaining importance in the field as the increasing democratisation and deployment of mobile computing, mobile devices and sensing technologies [196] provide new opportunities to deliver mobile mental health care [197][198][199] thus improving quality of life [200]. Various authors [199,201,202] have suggested that interventions with mobile phones designed to support evidence-based treatments could even reduce barriers to access and increase participation in treatment. The rapid and wide adoption of these new developments and technological innovations is leading to a new stream of research that explores the prevention of mental health disorders through mobile-based interventions [203].…”
Section: Introductionmentioning
confidence: 99%